Personal moral philosophy and ethical decision making of human resources practitioners in hotel industry - Chan, Ling Meng; Othman, Jamilah; Joned, Rusinah (2011)
This study attempted to study the relationship of personal moral philosophy and ethical decision making among human resources practitioners in hotel industry. Findings suggest that respondents’ Idealism Score and Relativism Score were significantly related to Ethical Decision Making Score. Through findings, evidences shows that human resources practitioners are absolutists (high idealism but low relativism). They believe individual should strive for produce the best consequences, but they need to follow the universal moral rules.